Computational fluid dynamics simulation study of the gas flow balance in a vertical HVPE reactor with a showerhead for low cost bulk GaN crystal growth. (28th May 2019) - Liu, Qiang; Fujimoto, Naoki; Nitta, Shugo; Honda, Yoshio; Amano, Hiroshi
Abstract: In order to make low cost bulk GaN single crystal with a high growth rate, we have built a vertical HVPE reactor with a showerhead configuration. The flow from the showerhead of the reactor is independently controlled by inner/outer two sets of gas supply lines. This special showerhead design makes the flow model different from the conventional showerhead reactors. We have employed a finite element-based simulator to study the fluid dynamic and crystal growth of this inner/outer flow independently controlled showerhead. Two simulation experiments were performed. One experiment has demonstrated that both growth rate and Ga yield can be improved without compromising the uniformity by controlling the different input parameters of inner and outer flow on the showerhead, as compared with the conventional showerhead. The other experiment has demonstrated that the showerhead can be further optimized by changing the inner/outer area ratio and input parameters.